An investigation into high school English language tearchers' belisfs and practice of group work in the english language teaching context of Ben Tre province : - Trần, Ngọc Thiên Phương (Trường Đại học Cần Thơ, 2010)
The main purpose of this to investigation into high school English language tearchers' belisfs and practice of group work & the extent to which these beliefs are reflected in their classroom practice.In addition, this study explores the contraints teachers face in applying group work in Vietnamese EFL context.